Vulnerabilidade socioambiental ao desconforto térmico em Ituiutaba (MG) - Dutra Júnior, Nelio Paulo Sartini (2017)
Studies on socioenvironmental vulnerability emerges in an attempt to understand how social relations and environmental characteristics can give rise to certain risks to certain localities. At this juncture, current discussions within the urban space highlight the need to understand how socio-environmental characteristics can make this space more or less vulnerable to thermal discomfort, given the growing local climate change. For the World Health Organization, the thermal discomfort is caused by the excess heat, and can reach critical situations of thermal stress. Ituiutaba, is one of the main cities of the Triangulo Mineiro, is located in the Cerrado Biome, and is known for having one of the highest temperatures in the micro-region. The thermal discomfort, in Ituiutaba (MG), is accentuating mainly in hot and dry months when the absence of rain is evident. This work aims to identify the spatialisation of socio-environmental vulnerability applied to thermal discomfort in the urban area of Ituiutaba-MG. The variables selected for the elaboration of the index of social vulnerability to thermal discomfort are supported by the theoretical assumptions of Health Canada (2011), World Health Organization (WHO) and studies by Almeida (2010), Rezende (2016) and Bortoletto and Freitas (2015). To do so, based on data from the IBGE Demographic Census of 2010, we used an exploratory factorial analysis technique to create 6 social vulnerability factors, as follows: Factor 1 Education and Income, Factor 2 Presence of the Elderly, Factor 3 Households Without basic sanitation, Factor 4 Household managers, Factor 5 Households without afforestation and Factor 6 Households with liquid and solid residues exposed. For the environmental vulnerability, images of Landsat 8, Google Earth, 2010 Census data and geoprocessing techniques were used to generate the synthetic indexes of environmental vulnerability: demographic density, urban afforestation, proximity to water / lakes and surface temperature by sector Census. As a result, it was identified that the neighborhoods with greater social vulnerability were Satelite Andradina, Santa Maria and eastern portion of the Independência neighborhood; And among the most vulnerable from an environmental point of view, we can mention Jardim Jamila, Morada do Sol and part of Jardim do Rosário.